Treadmill Bicycle By IJISRT - Jay D.Bhalekar; Ananya N.Tulaskar; Sabaji A.Sawant; Prathamesh S.Gosavi; Mehghasham P.Dhanji; Shruti N.Hewalekar (International Journal of Innovative Science and Research Technology (IJISRT), 2024)
The treadmill bicycle is an innovative exercise machine that aids in fitness and well-being. It resembles a regular bike but with a moving treadmill belt.This bike allows you to run or walk while pedaling at the same time, making it easy to use and comfortable with handlebars and a seat. When you use the treadmill to walk or run, you have the opportunity to control your speed and balance while pedaling, resulting in a full-body workout. This exercise is beneficial in terms of burning calories, improving your heart health, and working out your leg and arm muscles. Furthermore, it's an excellent choice for outdoor exercise, such as in parks or on trails, and it's also environmentally friendly. The best part is that it's gentle on your joints, so even if you have trouble moving around, you can still use it. The treadmill bicycle is designed to combine the enjoyment of biking with the benefits of walking or running on a treadmill, making exercise more enjoyable Everyone can access it.